Analisis Persaingan Tenaga Kerja Indonesia vs. India di Pasar Jepang dan Implikasinya bagi Kebijakan SDM Nasional - Razan Muhammad Hannan; Nawangga Ragafansa OI (JURNAL ILMIAH NUSANTARA, 2026)
This study analyzes Indonesia's strategic position in the competition for skilled and semi-skilled labor against India in the Japanese market, as well as its implications for National Resilience and National Human Resources (HR) Policy. Japan, facing an acute demographic crisis, has become a critical arena where the need for caregivers and manufacturing workers is balanced by high demand for Information Technology (IT) professionals. Using a comparative-analytical library research method, this paper finds that Indonesia's dominance in low-skill sectors creates migration vulnerability. This study suggests that Indonesia must reorient its HR policy from quantity to quality and vocational certification to enhance national competitiveness and maintain economic stability.